Canadian Physicians' Use of Perioperative Botulinum Toxin Injections to Spastic Limbs: A Cross-sectional National Survey - Farris Kassam, BSc; Sepehr Saeidiborojeni, MD; Heather Finlayson, MD, FRCPC; Paul Winston, MD, FRCPC; Rajiv Reebye, MD, FRCPC (Archives of Rehabilitation Research and Clinical Translation, 2021)
Objective: To investigate the practice patterns of Canadian physicians who use perioperative botulinum toxin (BoNT) injections to improve surgical outcomes on spastic limbs. Design: A cross-sectional national survey composed of an invitation email and an 18-item questionnaire was disseminated by a national physical medicine and rehabilitation (PMR) society to 138 physician members involved in spasticity management. Setting: Not applicable. Participants: Twenty-five percent of the participants (N=34) fully completed the survey. Interventions: Not applicable. Main Outcome Measures: Participants completed an online questionnaire that examined the practice patterns and surgical outcomes associated with perioperative BoNT injections. Results: The majority (n=21; 84%) of Canadian physicians who inject BoNT perioperatively to improve outcomes of surgeries performed on spastic limbs are specialists in PMR practicing in academic settings. Most respondents (74%) used BoNT injections for perioperative treatment for patients with limb spasticity undergoing surgery. Of those surveyed, 65% of physicians used BoNT preoperatively, 21% used BoNT intraoperatively, and 24% used BoNT postoperatively.Of the physicians who performed BoNT injections preoperatively, 6% performed BoNT injections 7 to 12 weeks preoperatively, 32% performed BoNT injections 4 to 6 weeks preoperatively, 47% performed BoNT injections 2 to 3 weeks preoperatively, and 15% performed BoNT injections 0 to 1 week preoperatively. The majority of physicians (85%) responded that injecting BoNT perioperatively may improve a patient's surgical outcome and all of the participants (100%) stated that BoNT did not contribute to any perioperative complications or adverse effects. Qualitative responses emphasized that successful outcomes from the perioperative BoNT were linked to enhanced collaboration with surgeons and that more research is needed to determine the optimal timing of perioperative BoNT. Conclusion: Canadian physicians, mostly PMR specialists, administer perioperative BoNT to improve outcomes of surgeries performed on spastic limbs. The optimal timing for perioperative BoNT was suggested to be 2 to 3 weeks before the surgery by 47% of survey respondents. All participating physicians responded that perioperative BoNT did not contribute to any known perioperative complications or adverse events. This study highlights the importance of conducting more robust research to better understand optimal timing for perioperative BoNT injection, enhancing collaboration between physicians and surgeons, and increasing awareness of perioperative BoNT when planning for surgeries on spastic limbs.